The Role and Importance of Space Factors in Plant Life - Djumaboevna, Janazakova Dilbarkhon; Daughter, Kholdarova Sevarakhon Rakhmatjon; Bozorboy Ogli, Masardinov Khushnudbek (European Journal of Life Safety and Stability (2660-9630), 2021)
Today, the agricultural sector is developing rapidly, bringing new modern agro-technologies and achieving high results. In the "Strategy of Action" developed in 2017, the head of our state Sh.M.Mirziyoev also paid special attention to agriculture and outlined the work to be done. This strategy is designed for five years and a number of works are underway to implement it. Each plant grows and develops by assimilating the external environmental factors it needs. Each of these factors plays an important role in plant life. Among these factors, space (spatial) factors (heat, light) stand out. The growth and development of plants depends on their supply of water, heat, light and air.